2021
DOI: 10.3390/ma14195657
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Method for Longer Effective Corrosion Inhibition Time: Controlled Release Oil Palm Empty Fruit Bunch Hemicellulose Inhibitor Tablet

Abstract: This study aims to develop a controlled release oil palm empty fruit bunch hemicellulose (EFB-H) inhibitor tablet for mild steel in 1 M HCl. As plant extracts tend to deteriorate at longer immersion time, limiting its industrial applicability, we attempted to lengthen the inhibition time by forming a controlled release inhibitor tablet. Electrochemical methods (potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS)) were employed to investigate the efficiency and mechanism of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Previous investigations on mild steel in simulated 3.5 % NaCl Solution showed that the inhibition e ciency of Jatropha Curcas and Hibiscus Sabdariffa Calynx increases with increase in inhibitor concentrations 33 and disorders in the digestive, genito-urinary, respiratory, dermal, endocrine, and cardiovascular system 39 . Investigative studies revealed that oil palm leaves, and empty fruits bunch have corrosion inhibitory properties [40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations on mild steel in simulated 3.5 % NaCl Solution showed that the inhibition e ciency of Jatropha Curcas and Hibiscus Sabdariffa Calynx increases with increase in inhibitor concentrations 33 and disorders in the digestive, genito-urinary, respiratory, dermal, endocrine, and cardiovascular system 39 . Investigative studies revealed that oil palm leaves, and empty fruits bunch have corrosion inhibitory properties [40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
“…Grape seed showed 88% IE at 300 ppm, according to Marhamati et al [12]. Mangifera indica [13], Nephelium lappaceum [14], Polygonatum odaratum [15], Flacourtia Jangomas [16], Cistus monspeliensis [17], Oil palm [18], kola leaf [19], Conocarpus Erectus [20], Morinda citrifolia [21], Theobroma cacao Peel [22], Pomegranate Peel [23], Cassia auriculata [24], Citrus Sinensis Seeds [25], Prunus persica [26], Calendula officinalis [27], Alchornea Cordifolia [28], Cucurbita [29], Mimosa pudica leaves [30], Syzygium aromaticum [31], Jatropha Curcas [32], Argemone Mexicana [33], and Veronia Amygdalina [34]…”
Section: Introductionmentioning
confidence: 99%